2017
DOI: 10.1002/jso.24618
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after surgery in patients with bone sarcoma around the knee; results from a long‐term prospective study

Abstract: Background and ObjectivesIn a previous conducted study functional outcome of young patients with bone sarcoma located around the knee was longitudinally evaluated during the first 2 years postoperatively. Functional outcome improved significantly over the first 2 years. The purpose of this descriptive study was to evaluate the functional outcome of these patients at long‐term follow‐up of 7 years.MethodsFunctional outcome was assessed with the TESS, MSTS, Baecke questionnaire, and three functional performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
13
0
5
Order By: Relevance
“…In addition to the Musculoskeletal Tumour Society Score and the Toronto Extremity Salvage Score, several new evaluation scales have been developed in recent years, and some have also been used for musculoskeletal tumours. [30][31][32][33][34] However, these methods of evaluation are disease-specific, and a generalized evaluation method remains to be developed for future evaluations. Davis et al reported that the Musculoskeletal Tumour Society Score and the Toronto Extremity Salvage Score demonstrate a significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Musculoskeletal Tumour Society Score and the Toronto Extremity Salvage Score, several new evaluation scales have been developed in recent years, and some have also been used for musculoskeletal tumours. [30][31][32][33][34] However, these methods of evaluation are disease-specific, and a generalized evaluation method remains to be developed for future evaluations. Davis et al reported that the Musculoskeletal Tumour Society Score and the Toronto Extremity Salvage Score demonstrate a significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Independentemente da presença de liberação, ou do tipo de reinserção, ocorre diminuição da força muscular dos flexores e extensores do joelho (KENDALL et al, 2000). Poucos estudos avaliam em detalhe a força muscular nessas diferentes situações (TSUBOYAMA et al, 1993;PETSCHNIG et al, 1995;BENEDETTI et al, 2000;PILGE et al, 2015) e comparam entre os tipos de reconstruções (BERNTHAL et al, 2015).…”
Section: Discussão 5 Discussãounclassified
“…Nossos resultados mostram reduções do pico de torque de 77,5% para extensão e 21,9% para flexão do joelho em relação ao membro não operado. Estudos anteriores relataram redução da força extensora do joelho de 52,6% a 91,0% (TSUBOYAMA et al, 1993;PETSCHNIG et al, 1995;BENEDETTI et al, 2000;BERNTHAL et al, 2015; PILGE et al, 2015). Neste estudo, não houve diferença na redução do pico de torque quando comparadas as ressecções femorais e tibiais.…”
Section: Discussão 5 Discussãounclassified
See 2 more Smart Citations